Projects for Intensive Development of Small Industries in Rural Areas - Planning Commission (Planning Commission, Government of India, 1962)
This document outlines the Government of India’s strategy for the intensive development of small industries in rural areas under the Third Five-Year Plan, as formulated by the Rural Industries Planning Committee. Recognizing that the majority of India’s population resides in rural areas, the initiative seeks to raise living standards through employment generation and economic diversification beyond agriculture. The programme emphasizes a comprehensive area-based approach that integrates agriculture, small industries, infrastructure, and social services. It proposes the establishment of small and village industries, along with the decentralization of selected larger industries into rural regions to promote balanced regional development. The selection of project areas is based on agricultural potential, population pressure, employment needs, and the development requirements of tribal and backward regions. Drawing on lessons from earlier pilot projects, the plan stresses the importance of detailed local surveys, community participation, skill development, and cooperative organization. The document concludes that sustainable rural industrialization requires coordinated planning, institutional support, adequate finance, and infrastructure, with the flexibility to evolve based on practical experience gained during implementation.
Rural Industries Planning Committee, Government of India Planning Commission
Rural Industries Planning Committee, Government of India Planning Commission
Keywords: Rural Industrialization; Small and Village Industries; Third Five-Year Plan; Rural Employment; Agro-Industrial Economy; Cooperative Development; Local Resource Utilization; Non-Agricultural Employment; Area Development Projects; Artisan Training; Balanced Regional Development; Rural Infrastructure